A LEAP based optimization model for generation expansion planning for the Philippines - Nobleza, Bryan Joseph C.
This thesis describes a LEAP-based optimization model for generation expansion planning for the Philippines through the application of LEAP-OSeMOSYS framework. The model, together with the correct set of assumptions and data, serves as a tool for energy planners to assess different Philippine energy policy scenarios in support for long term energy planning. The baseline model was based on 2015 Philippine power generation system following the Philippine grid and off-gird based regions: Luzon, Visayas, Mindanao, Palawan and Mindoro, thus, creating an independent multi-regional and a national scale structure. The baseline model results replicated the actual generation per technology and GHG emission of the base year 2015. The hypothetical Business-As-Usual (BAU) scenario results showed a drastic increase in Philippine electricity generation and generation capacity by 2050 compared with the base year. The model was used to simulate other scenarios, such a the impact of the NREP, an enhanced NREP, and the reactivation of the Bataan Nuclear power plant, among others. The results show that the NREP may produce a significant contribution RE technologies both in Philippine generation and capacity mix while decreasing the shares of natural gas and oil-based technologies. The hypothetical alternative scenarios result showed that the Double the NREP (DNREP) scenario may result in significant reduction in the cost of production and GHG emissions across all regions. Moreover, Luzon scenario results showed that the possible reduction on cost of production of Bataan Nuclear Power Plant (BNPP) and DNREP scenarios are approximately at part, and further results showed that doubling BNPP might surpass DNREP's potential cost reduction by a significant margin. Lastly, Palawan and Mindoro scenario results showed that the Optimization (OPT) scenario might have the highest potential reduction on cost of production leading to the lowest system LCOE, however, it produced the highest GHG emissions.